HUBUNGAN ADIKSI MEDIA SOSIAL DENGAN KONSENTRASI BELAJAR SISWA KELAS V SEKOLAH DASAR DI KELURAHAN KEBON JERUK - Trevina Hendrick, Ziva; Winarni, Susi; Syarif Sumantri, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between social media addiction and learning concentration among fifth-grade elementary school students in Kebon Jeruk Subdistrict, West Jakarta. This research employed a quantitative approach with a correlational method. The research sample consisted of 146 fifth-grade students selected using purposive sampling techniques. Data were collected through questionnaires measuring social media addiction and learning concentration using a Likert scale. Data analysis techniques included descriptive analysis and Spearman Rank correlation test. The results showed a negative relationship between social media addiction and students’ learning concentration. Higher levels of social media addiction were associated with lower learning concentration. These findings indicate the importance of parental and teacher supervision in controlling social media use among elementary school students.